2013
DOI: 10.1186/1297-9686-45-28
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection using low density marker panels with application to a sire line in pigs

Abstract: BackgroundGenomic selection has become a standard tool in dairy cattle breeding. However, for other animal species, implementation of this technology is hindered by the high cost of genotyping. One way to reduce the routine costs is to genotype selection candidates with an SNP (single nucleotide polymorphism) panel of reduced density. This strategy is investigated in the present paper. Methods are proposed for the approximation of SNP positions, for selection of SNPs to be included in the low-density panel, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 27 publications
(38 reference statements)
6
65
0
Order By: Relevance
“…Batches of these panels can be manufactured including private SNPs that can be read only by the owner of this information or including patented markers and SNPs in a few genes associated with production traits (Table 2). Other studies simulated the lower number of SNPs needed according to different scenarios of genotyping and imputation with higher density SNP chips to obtain sufficient predicting ability of GEBV (Wellmann et al 2013;Stratz et al 2014;Xiang et al 2015). For example, based on simulations, a panel size of less than 1000 markers spread all over the pig genome (with the lower limit of 384 markers), if imputed to a higher density panel genotyped in at least one of the parents, could be used to obtain unbiased estimates of accuracy of genomic breeding values (Wellmann et al 2013).…”
Section: Genomic Selection In Pig Populationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Batches of these panels can be manufactured including private SNPs that can be read only by the owner of this information or including patented markers and SNPs in a few genes associated with production traits (Table 2). Other studies simulated the lower number of SNPs needed according to different scenarios of genotyping and imputation with higher density SNP chips to obtain sufficient predicting ability of GEBV (Wellmann et al 2013;Stratz et al 2014;Xiang et al 2015). For example, based on simulations, a panel size of less than 1000 markers spread all over the pig genome (with the lower limit of 384 markers), if imputed to a higher density panel genotyped in at least one of the parents, could be used to obtain unbiased estimates of accuracy of genomic breeding values (Wellmann et al 2013).…”
Section: Genomic Selection In Pig Populationsmentioning
confidence: 99%
“…The accuracy obtained with the imputation depends on several factors, such as the number of markers in the LD panel, the markers informativeness and their distribution across the genome, the relationship between the genotyped animals, the effective population size and the used method of imputation (Wellmann et al 2013). The reduction in the accuracy of direct GEBV is ranging only between 0.02 and 0.05, depending on the reference base, and the average reliability increased with large training populations (Dassonneville et al 2011).…”
Section: Economic Aspects Of Genomic Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…the offspring) at very-low density, but impute to high density -a technique that is relatively commonplace in terrestrial livestock breeding (e.g. Wellmann et al, 2013) and has shown promise in Atlantic salmon breeding (Tsai et al, 2017).…”
Section: Future Directionsmentioning
confidence: 99%
“…The development of this type of chip is important to reduce genotyping costs. In animal breeding, low density chips for cattle (Heaton et al, 2002;Boichard et al, 2012) and pigs (Wellmann et al, 2013) have been developed. Moreover, the genotyping cost of a low density chip is much lower than that of a high density chip (Habier et al, 2009).…”
Section: Markers Density Versus Estimated Breeding Valuementioning
confidence: 99%